A multidimensional study of weak-form efficiency for finance stocks in Malaysia - Kok, Sook Ching (2017)
Finance sector plays a vital role in financial system. Nevertheless, it is exposed to systematic default risk, bank run, and shocks emanating from financial system. This thesis primarily aims to determine the weak-form efficiency for finance stocks in Malaysia, covering financial holding companies, commercial banks, investment banks, insurance companies, capital market intermediaries, and finance companies. The specific objectives of this study are: to examine the random walk properties for finance stock prices in Malaysia based on a random walk model that incorporates cross-sectional dependence (CD) and structural breaks; to examine nonlinearity and threshold effect of finance stock prices in Malaysia through a two-regime threshold autoregressive (TAR) approach, allowing for evaluating the random walk properties in separate regimes; to investigate the existence of calendar anomalies in the market of finance stocks in Malaysia by focusing on the day-of-the-week effect, month-of-the-year effect, turn-of-the-month (TOM) effect, and holiday effect; and to investigate the presence of short-term momentum effect and return reversal in the market of finance stocks in Malaysia. This study shows the following findings: 1) The prices of all finance stocks follow a random walk process hence weak-form efficiency is validated; 2) There is strong CD among the cross-sectional units of financial firms in Malaysia; 3) Each finance stock price series displays several structural changes throughout the study period; 4) The prices of all finance stocks are nonlinear and showing the threshold effect, thus reflecting basic human psychological influence that causes tension threshold and changing behaviour of efficiency across different regimes in the finance stock prices. The finance stocks are either fully or partially complying with the random walk properties and weakform efficiency; 5) Calendar anomalies occur in the market of finance stocks; 6) Short-term momentum effect and return reversal exist in the market of finance stocks, in which they are unexplainable within the efficient market paradigm; 7) As calendar anomalies, short-term momentum effect and return reversals are evident, the weak-form efficiency in short-term is invalid. The above findings suggest that the selected finance stocks in Malaysia are efficient in the weak-form sense based on a random walk model that incorporates CD and structural breaks, but inefficient in short-term. In addition, finance stock efficiency may change during times of extreme sentiment as finance stock prices reflect the effect of tension threshold.